Innerstädtische Grünflächen = kühl = entlastend? Eine Skizze zu klimatologischem Denken - Zahnen, Barbara (ERDKUNDE, 2004)
The essay enters into the question of the peculiarity of climatological thinking. The theoretical reflections, which are based upon the author’s practical experience in climatology taking into consideration hermeneutic-phenomenological positions, start off by focussing upon a specific kind of empirical climatology, which is often practiced in applied urban climatology and aims at the registration and description of boundary climate phenomena such as cool islands, local wind systems etc., by means of recording data in a limited way as to time and space. Using urban climatological examples, especially those concerning urban green areas or parks, this essay aims at affording a theoretical insight into such a way of climatological practice and characterizing its way of thinking. By this, however, dimensions and problems coming along with these dimensions are disclosed, which go beyond empirical urban climatology and also concern other methods and fields of climatology, especially the method of mathematical-physical modelling and the field of climate change. Hence, characteristic features of climatological thinking are revealed, which commonly are not expected and thus not explicated in a natural science, but inevitably belong to the science of climatology.